2018
DOI: 10.1051/0004-6361/201834079
|View full text |Cite
|
Sign up to set email alerts
|

The s process in AGB stars as constrained by a large sample of barium stars

Abstract: Context. Barium (Ba) stars are dwarf and giant stars enriched in elements heavier than iron produced by the slow neutron-capture process (s process). They belong to binary systems where the primary star evolved through the asymptotic giant branch (AGB) phase, during which it produced the s-process elements and transferred them onto the secondary, now observed as a Ba star. Aims. We compare the largest homogeneous set of Ba giant star observations of the s-process elements Y, Zr, La, Ce, and Nd with AGB nucleos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 115 publications
3
68
0
Order By: Relevance
“…The rotation induced mixing alters the extend of 13 C pocket (Langer et al 1999), which in turn affects the sprocess abundance pattern. However, a study made by Cseh et al (2018) using the rotating star models available for the metallicity range of Ba stars (Piersanti et al 2013) could not reproduce the observed abundance ratios of stars studied in de Castro et al (2016).…”
Section: Comparison With Fruity Models and A Parametric Model Based Amentioning
confidence: 95%
“…The rotation induced mixing alters the extend of 13 C pocket (Langer et al 1999), which in turn affects the sprocess abundance pattern. However, a study made by Cseh et al (2018) using the rotating star models available for the metallicity range of Ba stars (Piersanti et al 2013) could not reproduce the observed abundance ratios of stars studied in de Castro et al (2016).…”
Section: Comparison With Fruity Models and A Parametric Model Based Amentioning
confidence: 95%
“…All models show a clear trend with the yield of heavy s-process elements (Ba, Ce, Nd, Hf, W, Pt, Os) decreasing, relative to the light s-process elements, as the metallicity increases. Shown in panel Ce/Y are the observational data for Ba stars 51,92 in grey. These also indicate a decrease in the Ce/Y ratio as a function of increasing metallicity 51 .…”
Section: Extended Data Fig 5 | Elemental Ratios As a Function Of Metmentioning
confidence: 99%
“…In Fig. 4, we also show theoretical s-process predictions from two groups: the FRUITY 1 yields from Cristallo et al (2015), which cover a range in metallicity from [Fe/H] ≈ 0.1 to −2.3, and the 1 http://fruity.oa-teramo.inaf.it/ Monash yields (Fishlock et al 2014;Karakas & Lugaro 2016), which cover a range in metallicity from [Fe/H] = +0.3 to −1.2 (similarly to Cseh et al 2018). For both sets of models, we show results from initial masses between 1.5 and 3 M .…”
Section: Comparison To Agb Yieldsmentioning
confidence: 81%